2004
DOI: 10.1029/2003ja010208
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric electric fields and plasma sheet injection to low L‐shells during the 4–5 June 1991 magnetic storm: Comparison between the Rice Convection Model and observations

Abstract: .[1] The major magnetic storm of 4-5 June 1991 was well observed with the Combined Release and Radiation Experiment (CRRES) satellite in the duskside inner magnetosphere and with three Defense Meteorological Satellite Program (DMSP) spacecraft in the polar ionosphere. These observations are compared to results from the Rice Convection Model (RCM), which calculates the inner magnetospheric electric field and particle distribution self-consistently. This case study, which uses the most complete RCM runs to date,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 58 publications
(84 reference statements)
5
62
0
Order By: Relevance
“…showed that they were directly linked to the partial ring current localized pressure peak, and other observations and numerical modeling has confirmed and further quantified this relationship (e.g. Garner et al 2004;Mishin and Burke 2005;Yu et al 2015;Yuan et al 2016;Califf et al 2016). SAPS are relatively stable during storms, being a persistent feature across the evening sector that can last for many hours (e.g.…”
Section: Ring Current and Ionosphere And Thermospherementioning
confidence: 75%
“…showed that they were directly linked to the partial ring current localized pressure peak, and other observations and numerical modeling has confirmed and further quantified this relationship (e.g. Garner et al 2004;Mishin and Burke 2005;Yu et al 2015;Yuan et al 2016;Califf et al 2016). SAPS are relatively stable during storms, being a persistent feature across the evening sector that can last for many hours (e.g.…”
Section: Ring Current and Ionosphere And Thermospherementioning
confidence: 75%
“…The subauroral polarization stream (SAPS) is one of the interesting and important features of the magnetosphereionosphere-thermosphere coupling processes in the subauroral region, representing the rapid westward plasma flow predominantly in the dusk and premidnight sector (16-24 magnetic local time, MLT) (e.g., Galperin et al, 1974;Spiro et al, 1979;Anderson et al, 1991Anderson et al, , 1993Anderson et al, , 2001Yeh et al, 1991;Fejer and Scherliess, 1998;Scherliess and Fejer, 1998;Rowland and Wygant, 1998;Wygant et al, 1998;Ridley et al, 2002;Foster and Vo, 2002;Garner et al, 2004;Figueiredo et al, 2004;Liemohn et al, 2005;Jensen and Fejer, 2007;Zheng et al, 2008;Erickson et al, 2010Erickson et al, , 2011Clausen et al, 2012;Mishin, 2013). Two types of plasma flows have been classified in the literature: (1) polarization jets (PJ) (Galperin et al, 1974) or subauroral ion drifts (SAIDS) (Spiro et al, 1979), featured as more intense (∼ 1000 m s −1 ) and latitudinally confined (≤ 1 • latitude) plasma flow; and (2) a wider latitudinal extent and longer duration of plasma flow (Yeh et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…While the magnitude becomes much smaller, the penetration effect continues into the recovery phase of the storm, indicating that the shielding is never strong during the event as previously discussed by Garner et al (2004). The continuous penetration is unexpected from the strong shielding previously estimated by Spiro et al (1988) in which the strong shielding was established after steady conditions were maintained for an hour or more.…”
Section: Model Results Of the 2september 2011 Stormmentioning
confidence: 63%
“…Furthermore, the time dependent boundary location is also required for the electrodynamic potential solver that specifies the boundary condition separating out the equatorward region of the self-consistent calculation from the region with the polar cap potential specified by the input model. Previous studies showed that higher plasmasheet temperature or smaller plasmasheet density generates weaker shielding and a more penetrating electric field at lower latitudes (Spiro et al, 1988;Garner et al, 2004). As input parameters, the RCM requires PV 5/3 (where P is thermodynamic pressure; V is flux tube volume, 5/3 is gamma) and TV 2/3 at 13 R E in the plasmasheet to be estimated from a statistical model, Tsyganenko and Mukai (2003) for this study.…”
Section: Model Results Of the 2september 2011 Stormmentioning
confidence: 99%